Diuretic Therapy in Heart Failure – Current Approaches - Casu, Gavino (Eur Cardiol, 2015)
The use of diuretics is common in patients with heart failure (HF), to relieve the congestive symptoms of HF. Although they are widely used, there are limited data on their ability to modulate HF-related morbidity and mortality. Diuretic efficacy may be limited by adverse neurohormonal activation and by ‘congestion-like’ symptoms. Diuretics are an extremely useful and varied class of agent for the management of hypervolaemic states. This review summarises the basic features of diuretics, including their mechanism of action, indications and adverse effects in heart failure.